2017
DOI: 10.3340/jkns.2016.0505.010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Percutaneous Sacroplasty on Pain and Mobility in Sacral Insufficiency Fracture

Abstract: ObjectiveSacral insufficiency fracture (SIF) contributes to severe low back pain. Prolonged immobilization resulting from SIF can cause significant complications in the elderly. Sacroplasty, a treatment similar to vertebroplasty, has recently been introduced for providing pain relief in SIF. The purpose of this study is to investigate the clinical short-term effects of percutaneous sacroplasty on pain and mobility in SIF.MethodsThis study is conducted prospectively with data collection. Sixteen patients (3 men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In our collective, 94 patients received percutaneous sacroplasty in local anesthesia. In line with other study groups, sacroplasty remaines to be one of the most important treatment for the majority 5 , 14 , 15) .…”
Section: Discussionsupporting
confidence: 75%
“…In our collective, 94 patients received percutaneous sacroplasty in local anesthesia. In line with other study groups, sacroplasty remaines to be one of the most important treatment for the majority 5 , 14 , 15) .…”
Section: Discussionsupporting
confidence: 75%
“…In particular, cement leakage with the risk of postoperative nerval lesion is to be mentioned. Numerous authors have demonstrated the low perioperative risk (especially with CT control) and the often asymptomatic perineural cement leakage 9 , 23 . In the patient material presented here there was one case of cement leakage, which led to a low-grade foot lift weakness of 4/5 after Janda.…”
Section: Discussionmentioning
confidence: 99%
“…Anteroposterior 3) and lateral 4) radiographs that show the polymethylmethacrylate cement in the sacral wing without leakage. 6 Figure 5. Postoperative radiograph that shows bilateral sacroiliac screws and consolidation of the fracture of the pubis.…”
Section: Discussionmentioning
confidence: 99%